L’antropologia storica fra antropologia e storia - Carle, Lucia (Scienze del Territorio, 2017)
The different orientations of historical anthropology in various countries depend largely on the type of anthropology that historians have faced. Since the 1960s, the environment of the Annales has led to a strong interest to introduce historical anthropology as a new discipline with its own methods and research fields, mediated by anthropology and history. Today at the international level historical anthropology has taken very different directions, developing interests which are not always parallel. In Italy, since its origins, it appears not as a specific discipline, native or imported, but rather as a meeting area between historians and anthropologists. Many historians practice it at least occasionally. Many anthropologists, as well, introduce elements of historical anthropology in their courses or practice it in their research. In 2004, the activation of the academic teaching of Historical anthropology of human settlements at the Empoli school of the University of Florence, activated since 2004, was motivated by a strong interest in a method of historical and anthropological research, already applied to investigations about identity, that was deemed useful in the territorial analysis preliminary to plans in order to depict the collective social identity of the population in the relevant territories. As a part of territorial sciences in a territorialist view, the contribution of historical anthropology to the survey of the human components of territorial nexuses turns often out as essential.